Performance of expanded non-invasive prenatal testing for fetal aneuploidies and copy number variations: A prospective study from a single center in Jiangxi province, China - Zou, Yongyi; Feng, Chuanxin; Qin, Jiawei; Wang, Xinrong; Huang, Tingting; Yang, Yan; Xie, Kang; Yuan, Huizhen; Huang, Shuhui; Yang, Bicheng; Lu, Wan; Liu, Yanqiu (Frontiers in Genetics, 2023)
To evaluate the performance of expanded noninvasive prenatal testing (expanded NIPT, NIPT-Plus) in screening for fetal chromosomal abnormalities includes aneuploidies and copy number variations, a total of 23,116 pregnant women with a singleton pregnancy were recruited for NIPT-Plus. Screening positive results were verified by karyotype analysis and chromosomal microarray analysis after amniocentesis. A total of 264 pregnancies (1.14%) were positive results as predicted by NIPT-Plus, including 233 aneuploidies and 31 copy number variations. Following genetic counseling, 233 (88.26%) pregnant women underwent invasive prenatal diagnosis and 136 were verified as true positives, comprising 72 common trisomies (T21, T18, T13), 47 sex chromosomal abnormalities (SCAs), 2 rare autosomal aneuploidies (RATs) and 15 copy number variations (CNVs). The positive predictive value (PPV) for common trisomies, SCAs, RATs and CNVs were 68.57%, 68.12%, 6.67% and 51.72%, respectively. Pregnant women with screen-positive results for common trisomies have higher rates of invasive prenatal diagnosis and pregnancy termination than those with positive results for SCAs, RATs, and CNVs. NIPT-Plus showed a good performance in detecting common trisomies, SCAs and also contributed to detecting pathogenic CNVs, but higher accuracy was required in the detection of RATs. In summary, this study provides a reference for the clinical application of NIPT-Plus for screening fetal chromosomal abnormalities in this region. Therefore, we suggest that NIPT-Plus could be widely used in clinical screening for fetal chromosomal abnormalities in combination with prenatal diagnosis and genetic counseling.